Elite transition : from apartheid to neoliberalism in South Africa - Bond, Patrick (Pluto Press ; University of Natal Press, 2000)
In Elite Transition, Patrick Bond examines the economic and social compromises that have been, and are being, made between the past and present powers in South Africa. A former adviser to the ANC, Bond investigates how groups such as the ANC went from being a force of liberation for all people to a vehicle now perceived as serving the economic interests of an elite few. Bond covers a range of socioeconomic factors under both the old and new South Africa, highlighting the reasons for the transition's 'development' failure and drawing on case studies on key issues: social contracts, black economic empowerment, housing and corporate power. He explores the idea that progressive policymaking is being compromised by the new petit bourgeoisie and ruling elite, and assesses the view that, as change slows down, official policy is increasingly one of lower expectations.